IT Service Management System Measurement using ISO20000-1 and ISO15504-8: Developing a Solution-Mediated Process Assessment Tool to Enable Transparent and SMS Process Assessment - Imam Asrowardi; Septafiansyah Dwi Putra; Eko Subyantoro; Norzaidi Haji Mohd Daud (Institute of Advanced Engineering and Science, 2018)
Information technology is about not only hardware, software, communication infrastructure and communication infrastructure but also how to manage services. Information technology plays an increasingly important role in developing the structure and functions of public and private sectors. Service measurement plays an important role in IT service management (ITSM) that is one of the subfields of Services Computing science. ITSM is a big part of service science, a science field that combines computer science, operation research engineering, business strategy, management science, and organizational theory. Performance measurement from each of IT services is absolutely needed and is important in the continuous development of ITSM. These research provide good technical knowledge about the measuring ITSM with some requirements. In this paper we suggest the metrics in each service processes enables organizations to predict a direction for active process enhancement and to identify if the goal of process can achieve. This objective process metrics based on ISO/IEC 15504-8 and PRM ISO/IEC 20000-4 refinement. The output of this research, in the form of metrics and tools for any type organizational use.